Telecommunication circuit design - Van der Puije, Patrick D. (Wiley series in telecommunications, 1992)
This new edition of the popular guide to telecommunications circuit design offers the same comprehensive coverage found in the first edition, but now features additional sections on mobile and wireless phones and pagers, compact antennas, switches, power amplifiers, and TDMA and CDMA modulation schemes. Also new to this edition is a chapter devoted to the design of cellular phones, as well as new end-of-chapter exercises.